THE EFFECT OF THE INFLUENCE OF PRODUCTS, PRICES, PROMOTIONS AND BRAND IMAGE ON SALES VOLUME IN CAHAYA MANDIRI TRADING BUSINESS - Hermanto; Yudha Remofa; Heriasman (International Journal of Social Science, 2021)
The research was conducted at Cahaya Mandiri Trading Business, with the aim of seeing the effect of Product, Price, Promotion and Brand Image Effect on Sales Volume at Cahaya Mandiri Trading Business. The sample in this study were 87 consumers. The type of data used in this study is primary data in the form of quantitative data which is carried out by distributing questionnaires to consumers who shop. The analytical tool that the author uses is Multiple Linear Regression Analysis with a quantitative approach with the help of SPSS Software Version 21. The results of the study can be concluded that: (1) The product partially has a significant effect on Sales Volume at Cahaya Mandiri Trading Business. (2) Price partially has a significant effect on Sales Volume at Cahaya Mandiri Trading Business. (3) Promotion partially has a significant effect on Sales Volume at Cahaya Mandiri Trading Business. (4) Brand Image partially has a significant effect on Sales Volume at Cahaya Mandiri Trading Business. (5) Product, Price, Promotion and Brand Image simultaneously have a significant effect on Sales Volume at Cahaya Mandiri Trading Business.